Legal Regulation of the Doctor-Patient Relationship in the Czech Republic: Development and Current State, with a Practical Focus on Gynecology and Obstetrics - Schwarzová, Aneta (Bioethica, 2024)
The article focuses on the development of the relationship between doctor and patient and subsequent legal regulations in the Czech Republic from the beginning of the 20th century to the present. First, it delves into the evolution of the relationship between doctor and patient in the territory of the Czech Republic, providing an overview of important historical events that profoundly influenced the creation of sources and some institutes. Subsequently, it analyzes the current situation in the Czech Republic, subjecting it to a critical evaluation. The author, above all, questions whether the relationship between doctor and patient is truly a partnership and an equal one. The article then addresses persistent inequalities and differences between the rights and obligations of the patient and the doctor. The conclusion acknowledges that, considering the nature of the relationship, it may not be possible to completely eliminate these persistent inequalities. Based on the findings, partial conclusions are formulated, summarizing the individual stages and transformations of this relationship. The analysis of the current state of the relationship between doctor and patient includes a focus on important judicial decisions from practice and how they set limits for the autonomy of the patient's will. In this article, the author primarily concentrates on significant court decisions in the field of gynecology and obstetrics, analyzing how the autonomy of the patient's will is limited in this area in relation to specific situations.